TRANSFORMASI SPIRITUAL TOKOH UTAMA DALAM NOVEL ATEIS KARYA ACHDIAT KARTAMIHARDJA - Agus Yulianto (MABASAN, 2017)
The aim of this research is to know the reason of Hasan, the protagonist being anatheist and how the spiritual changing process from a devoted muslim into an atheistand how Islamic thougth denies ateism. The problems in this research are 1) whatcausing Hasan becoming an atheist; 2) how Hasan spiritually changes from adevoted muslim into an atheist; 3) how Islamic thought denies atheism.This studyuses qualitative descriptive method in literature review. Based on the study, it isconcluded that the causes of Hasan’s spiritual changing from a devoted muslim intoan ateist are his weaknees in Islamic thinking tradition and love factor which doesnot follow religious norms and ethics.